The Effect of Battery Manufacturing Under Different Conditions and Its Contribution to CO Emissions - Putra, Mufti Reza Aulia; Nizam, Muhammad; Setiawan, Bagas; Santoso, Henry Probo (Universitas Sebelas Maret, 2025)
Lithium-ion (Li-ion) batteries play a crucial role as energy sources for electric vehicles and portable electronic devices due to their high energy density. However, this high energy density leads to increased temperatures during operation, which negatively impacts the performance of nickel strips as the primary electrical connectors within the battery. Suboptimal welding of nickel strips results in safety issues, evidenced by gas leaks from the battery. This research aims to explore the impact of welding defects on battery performance, considering the role of gas sensors in enhancing safety. The test samples used are nickel strips with a thickness of 0.1 mm and a width of 5 mm, evaluated using varying currents of 10A, 20A, 40A, and 50A at room temperature. Observations were made regarding nickel degradation, followed by an analysis of carbon monoxide (CO) and carbon dioxide (CO₂) emissions. The results indicate a temperature increase of up to 78,8°C at the nickel tip, along with the identification of three welding points representing efficient values. Furthermore, the welding results on the battery produced microstructural defects that led to an increase in CO emissions by 18 ppm and CO₂ emissions by 500 ppm during the 1C charging process until reaching 100%.